Is the humoral immunity dispensable for the pathogenesis of psoriasis?. (2nd July 2018) - Thomas, J.; Küpper, M.; Batra, R.; Jargosch, M.; Atenhan, A.; Baghin, V.; Krause, L.; Lauffer, F.; Biedermann, T.; Theis, F.J.; Eyerich, K.; Eyerich, S.; et al.
Abstract: Background: Imbalances of T‐cell subsets are hallmarks of disease‐specific inflammation in psoriasis. However, the relevance of B cells for psoriasis remains poorly investigated. Objective: To analyse the role of B cells and immunoglobulins for the disease‐specific immunology of psoriasis. Methods: We characterized B‐cell subsets and immunoglobulin levels in untreated psoriasis patients ( n = 37) and compared them to healthy controls ( n = 20) as well as to psoriasis patients under disease‐controlling systemic treatment ( n = 28). B‐cell subsets were analysed following the flow cytometric gating strategy based on the surface markers CD24, CD38 and CD138. Moreover, immunofluorescence stainings were used to detect IgA in psoriatic skin. Results: We found significantly increased levels of IgA in the serum of treatment‐naïve psoriasis patients correlating with disease score. However, IgA was only observed in dermal vessels of skin sections. Concerning B‐cell subsets, we only found a moderately positive correlation of CD138 + plasma cells with IgA levels and disease score in treatment‐naïve psoriasis patients. Confirming our hypothesis that psoriasis can develop in the absence of functional humoral immunity, we investigated a patient who suffered concomitantly from both psoriasis and a hereditary common variable immune defect (CVID) characterized by a lack of B cells and immunoglobulins. We detected variants in three of the 13 described genes of CVID and a so far undescribed variant in the ligand of the TNFRSF13B receptor leading to disturbed B‐cell maturation and antibody production. However, this patient showed typical psoriasis regarding clinical presentation, histology or T‐cell infiltrate. Finally, in a group of psoriasis patients under systemic treatment, neither did IgA levels drop nor did plasma cells correlate with IgA levels and disease score. Conclusion: B‐cell alterations might rather be an epiphenomenal finding in psoriasis with a clear dominance of T cells over shifts in B‐cell subsets.